Mutasi Udp- Glucosyltransferase (Ugts) Gene Melalui Crispr/Cas9 Untuk Meningkatkan Kandungan Sakuranetin Pada Tanaman Padi - Niar Pramiswari Luki Hadi (Fakultas Pertanian, 2025)
Sakuranetin is one of the flavonoid group compounds that also has a pharmaceutical role because it is very useful when consumed. Sakurantein has several benefits such as anti-inflammatory, anticancer, antidibates, and others. Naringenin as the main precursor in the formation of sakuranetin is often conjugated by UDP-Glycosyl Transferase (UGTs) sugar groups. This causes naringenin to be formed into other compounds. Therefore, in this study, genetic modification was carried out using the CRISPR/Cas9 system to silence the UGTs gene. This research was conducted in 3 stages, namely design and construction of sgRNA, plasmid transformation into agrobacterium , and agrobacterium transformation in rice callus. The results obtained were obtained positive agrobacterium contained plasmid pRGEB32 as indicated by the results of plasmid sequencing. Agrobacterium transformation into rice callus showed a positive response in pandan wangi and koshihikari varieties. This is indicated by the high number of surviving callus explants.
Reuplod Repository Ratna 17 Juli 2026 Validasi dan Finalisasi Ratna 17 Juli 2026
Keywords: Genome Editing; Transformant plants; sgRNA; UGTs